(y-7)2=25

Take the square root of each side of the equation to set up the solution for y

(y-7)2⋅12=±25

Remove the perfect root factor y-7 under the radical to solve for y.

y-7=±25

Rewrite 25 as 52.

y-7=±52

Pull terms out from under the radical, assuming positive real numbers.

y-7=±5

y-7=±5

First, use the positive value of the ± to find the first solution.

y-7=5

Move all terms not containing y to the right side of the equation.

Add 7 to both sides of the equation.

y=5+7

Add 5 and 7.

y=12

y=12

Next, use the negative value of the ± to find the second solution.

y-7=-5

Move all terms not containing y to the right side of the equation.

Add 7 to both sides of the equation.

y=-5+7

Add -5 and 7.

y=2

y=2

The complete solution is the result of both the positive and negative portions of the solution.

y=12,2

y=12,2

Solve for y (y-7)^2=25